ЦИВІЛІЗАЦІЙНИЙ АНАЛІЗ У КРАЇНОЗНАВЧИХ СТУДІЯХ: ТЕОРЕТИКО-МЕТОДОЛОГІЧНИЙ АСПЕКТ (Zaporizhzhia Historical Review, 2021)
In the article the author examines the ways of applying civilizational analysis to the research of different countries. The approach offered here is embedded in N.Lumanís sociological theory of communications and the theories of consciousness in modern psychology. The author builds up on it by constructing a structural dynamic model of a local civilization with an eye on its use in country studies.